Development of mathematical skills at the cognitive level of basic general education students - Rodríguez-García, Vanessa Lucía Giuseppina; Reye-Meza, Orley Benedicto (International research journal of management, IT and social sciences, 2022)
The objective of the research was to evaluate the development of mathematical skills at the cognitive level of Basic General Education students of the Magaly Masson de Valle Carrera Educational Unit in the 2022, that in view of the learning results of the students and that according to national evaluations, the students did not reach the established average according to the evaluations carried out in Ecuador, they present a low cognitive level and a limited development of mathematical skills, for reasons of teacher training in technological and virtual tools, connectivity and the accompaniment of a significant adult at home. In the study, the theory of cognitive development is proposed, who explains how these are developed in the child and how their contribution helps to solve problems, which configure logical connections for the understanding of life situations. The level of the investigation was descriptive and explanatory; the quantitative approach, using scientific, inductive, deductive, analytical, synthetic, and statistical methods. The result was no relationship of mathematical skills in proportion to the cognitive level, in addition to the development of skills in children who had synchronous connectivity was high, who do not accept the virtual class system.